Analysis of Critical Thinking Skills in Decision Making with R Project in Mathematical Statistics Course - Rani Farida Sinaga; Lolyta Damora Simbolon; Efron Manik; Sofy Kristiani Manalu (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze how the use of R Project Software in mathematical statistics courses can contribute to improving students' critical thinking skills, especially in the context of data-based decision making. Indicators of critical thinking in decision making with R Project: 1) interpretation (can write what is known and asked in the question clearly or identify the problem correctly); 2) analysis (can write what must be done in solving the problem); 3) inference (can draw conclusions from what is asked logically and visualize the results); 4) evaluation (can write down the solution to the problem and build a model to evaluate alternatives); and 5) explanation (can provide reasons for the conclusions drawn). The research method uses a descriptive quantitative approach. This research has a population of 80 students with a sample size of 40 students using non-probability sampling with the purposive sampling technique. By using a significance level of 5% and a df value of nk = 40 - 2 = 38, the ttable value is 1.686. The tcount value of 3.383 exceeds the ttable value of 1.686, indicating that the null hypothesis is rejected at a 95% confidence level. And, keep the abstract concise by stating only the conclusion of the statistical test (significant positive effect). Thus, R Project can be recommended as a natural analysis tool for learning mathematical statistics.